2017
DOI: 10.1002/jcop.21843
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Theory of Sense of Community and Community Responsibility in Organizations: An Empirical Assessment of Predictive Capacity on Employee Well‐being and Organizational Citizenship

Abstract: This study attempts to advance our understanding of the experience of community in organizational settings by empirically testing a theory of sense of community responsibility (SOC‐R) in relation to traditional measures of sense of community [SOC] on outcomes of employee well‐being and organizational citizenship. Findings support the notion that SOC is a better predictor of employee well‐being, while SOC‐R more strongly predicts organizational citizenship behavior. The findings add new knowledge to the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 66 publications
8
78
0
1
Order By: Relevance
“…Boyd, Nowell, Yang, and Hano () examined the extent to which SOC and SOC‐R were associated with employee well‐being and engagement in public service employment settings, finding that SOC‐R was a better predictor of organizational citizenship behaviors, whereas SOC had a stronger association with job satisfaction. Similar findings were presented by Boyd and Nowell (), which confirmed that SOC and SOC‐R were distinct constructs, and SOC‐R more strongly predicted organizational citizenship behavior, whereas SOC had a stronger association with employee well‐being.…”
Section: Introductionsupporting
confidence: 87%
“…Boyd, Nowell, Yang, and Hano () examined the extent to which SOC and SOC‐R were associated with employee well‐being and engagement in public service employment settings, finding that SOC‐R was a better predictor of organizational citizenship behaviors, whereas SOC had a stronger association with job satisfaction. Similar findings were presented by Boyd and Nowell (), which confirmed that SOC and SOC‐R were distinct constructs, and SOC‐R more strongly predicted organizational citizenship behavior, whereas SOC had a stronger association with employee well‐being.…”
Section: Introductionsupporting
confidence: 87%
“…Given the efficacy of SOC‐R as an important and useful community experience construct, the current study tests if SOC‐R measures can be cross‐validated in the Italian context, and tests whether SOC‐R measures reveal adequate convergent and discriminant validity with SOC and other key correlates and outcomes. As stated above, according to the Community Experience Model (Boyd & Nowell, 2017; Nowell & Boyd, 2014), key correlates and outcomes of SOC‐R are well‐being, satisfaction, and community engagement and participation. In the next paragraphs, we will discuss the role of other potential key correlates and outcomes of SOC‐R that have not been investigated in the literature.…”
Section: Soc‐r and Soc As Distinct Aspects Of The Community Experiencementioning
confidence: 99%
“…The weakening of organizational identification will reduce miners' sense of responsibility in safeguarding the overall interests of the group and the organization [73], and subsequently result in decreasing OCB that is conducive to the safe operation of coal mining enterprises [74]. For instance, miners will not sacrifice their free time to demonstrate individual-level OCB such as extra occupational training.…”
Section: The Mediating Effect Of Organizational Identification On Thementioning
confidence: 99%